Islamic Educational Institutions According to KH. Ahmad Dahlan - Aisyatul Farhah; Abd Rahman Assegaf (Universitas Islam Lamongan, 2026)
In today's world, education is a never-ending topic. Islamic education is a discipline that plays a crucial role in the Muslim community. Within Islamic education, the scope is influenced by various perspectives of educational figures, thus becoming theories that serve as the foundation for Islamic education. K.H. Ahmad Dahlan was one such figure who placed a significant emphasis on Islamic educational institutions. Therefore, the focus of this paper is the concept of Islamic Educational Institutions according to K.H. Ahmad Dahlan. The purpose of this study is to understand the concept of Islamic Educational Institutions according to K.H. Ahmad Dahlan. This study uses qualitative data and library research. The results of the data analysis indicate that Islamic Educational Institutions are educational institutions aimed at developing a holistic Muslim personality. According to K.H. Ahmad Dahlan, the purpose of Islamic Educational Institutions is to shape a person's personality into a superior human being. In addition, his educational thought emphasizes the integration of religious and general sciences in the learning process.